PENGARUH HARGA LOKASI DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA WARUNG MAKAN PECEL LELE PAKDE KUMIS ALFALAH CIBINONG - ., Mujito; Rohma Devi, Oktaviani (Economicus, 2022)
This study aims to determine the effect of price, location, and product quality on purchasing decisions at Warung Makan Pecel Lele Pakde Kumis Alfalah Cibinong. This type of research is quantitative causality. The sample in this study was 100 customers who visited and bought at Warung Makan Pecel Lele Pakde Kumis Alfalah Cibinong. Data collection techniques using questionnaires. The data analysis technique used is multiple linear regression analysis. Based on the F test shows that the price, location, and product quality simultaneously or simultaneously have a significant effect on purchasing decisions. The results of the t-test (partial) that the price variable has a positive and significant effect on purchasing decisions, the location variable has a positive and significant effect on purchasing decisions, and the product quality variable has a positive and significant effect on purchasing decisions. Based on the adjusted R-square value, it can be seen that the variable price, location, and product quality have a simultaneous effect on purchasing decisions of 0.339 or 33.9% while the remaining 66.1% is influenced by other factors outside the variables studied by the researcher.